Optimum design of a three-dimensional serial robot manipulator - Snyman, J. A.; Tonder, F. (Structural Optimization, 1999)
A systematic and mathematical optimization methodology is presented for the optimal design of a three link, revolute joint, three-dimensional manipulator which must perform specific prescribed tasks. The objective of interest is the minimization of average torque requirement. In particular circular and eccentric closed task paths are considered. The optimization is carried out with the link lengths and the positional coordinates of the base taken as the five design variables, and subject to assembly and geometric constraints imposed on the system. In particular restrictions are placed on the joint angle between the links and on the link lengths. The minimization is successfully performed by the application of Snymans robust dynamic trajectory method for unconstrained optimization, to a penalty function formulation of the constrained problem.